Twitter-Controlled Microcontroller System For Home Automation - Muhammad Gaddafi bin Rusli, Muhammad Gaddafi (2010)
This project is significance in a sense that it can improve the lifestyle of the targeted group in having an alternative control over their premise without the physical presence in that particular premise. It is implemented by making use of the existing platform available in the Twitter infrastructure and wide audience, as a unique means of transmitting information and instruction.